Still surprised a memoir of a life in leadership - Bennis, Warren G. (Jossey-Bass, 2010)
"An intimate look at the founding father of the modern leadership movement Warren Bennis is an acclaimed American scholar, successful organizational consultant and author, and an expert in the field of leadership. His much awaited memoir is filled with insights about the successes and failures from his long and storied life and career. Bennis' life and career have traversed eight decades of first-hand experience with tumultuous episodes of recent history-from Jewish child in a gentile town in the 30's, a young army recruit in the Battle of the Bulge to a college student in the one of the first progressive precursors to the civil rights movement to a patient undergoing daily psychoanalysis for five years, and later a university provost during the Vietnam protests. Reveals the triumphs and struggles of the man who is considered the pioneer in the contemporary field of leadership studies Bennis is the author of 27 books including the bestseller On Becoming a Leader. This is first book to examine the extraordinary life of Warren Bennis by the man himself."--